(3JfHjg GdSGdc Ydi eXGf GdgGdcs - (3CHh HcQ Hf eMeO Hf YHO GdeDef Hf nMpQjR Hf eYnqdj GdMSjfj GdMUfj, Jbqj GdOjf,J (B829 (3g` s ((3YHO Gddg Hf eMeO GdYbQHGfi GdTGaYi s)
(3ChdgG (B:s
(3hHYO agPG ReGf jMb def QVi HGddg EYde Cf daX GdSeGY ai ReGfffG gPG ehVhY HGdGTJQGc s
(3BNQgG (B:s
(3hGYde Gf GdJhSd Hg Ydjg GdUdGI hGdSdGe eYfGg CSCd Gddg YR hLd HQShd hGJTaY Hg Edjg agh SGFd Gddg YR hLd dG dZjQg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B69 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B74s
Keywords: (3GdJUha hGdBOGH GdTQYjIs